2018
DOI: 10.1038/s41467-018-02898-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic allocation of orthogonal ribosomes facilitates uncoupling of co-expressed genes

Abstract: Introduction of synthetic circuits into microbes creates competition between circuit and host genes for shared cellular resources, such as ribosomes. This can lead to the emergence of unwanted coupling between the expression of different circuit genes, complicating the design process and potentially leading to circuit failure. By expressing a synthetic 16S rRNA with altered specificity, we can partition the ribosome pool into host-specific and circuit-specific activities. We show mathematically and experimenta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 38 publications
(49 reference statements)
1
87
0
Order By: Relevance
“…natriegens intrinsically has many desirable characteristics for a bioproduction chassis: Fast growth rate, genetic tractability, biological safety, and growth on a wide variety of carbon sources [4][5][6][7][8][9][10][11][12][13]46]. In regards to growth rate in particular, it has been shown that expression of some heterologous genes can decrease expression of others, due to competition for finite resources in the cell such as RNA polymerase and ribosomes [47,48]. One could expect that fast growth would require more demand on these finite resources, which would then be less available for heterologous expression and a liability for bioproduction.…”
Section: Discussionmentioning
confidence: 99%
“…natriegens intrinsically has many desirable characteristics for a bioproduction chassis: Fast growth rate, genetic tractability, biological safety, and growth on a wide variety of carbon sources [4][5][6][7][8][9][10][11][12][13]46]. In regards to growth rate in particular, it has been shown that expression of some heterologous genes can decrease expression of others, due to competition for finite resources in the cell such as RNA polymerase and ribosomes [47,48]. One could expect that fast growth would require more demand on these finite resources, which would then be less available for heterologous expression and a liability for bioproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Gorochowski et al 15 showed that transcriptional profiles can be used to debug failure modes of various gene circuits. Most recently, Rugbjerg and colleagues 16 coupled metabolite production to the expression of essential endogenous genes, which allowed to exploit evolutionary forces and increase production, while Darlington et al engineered a system that alleviates resource bottlenecks via an orthogonal ribosome 17 . Recent work further showed that promoters linked to the heat shock response of E. coli respond to heterologous expression, and then employed them to build a CRISPR/dCas9-based feedback system to control expression 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been proposed to counteract the effects of resource competition, either by finetuning the parameters in the gene circuit 5,7 or manipulating the size of the orthogonal resource pools [31][32][33][34] . Additionally, a burden-driven negative feedback loop was implemented to control gene expression by monitoring the cellular burden [35][36][37] .…”
Section: Resource Competition Is Commonplace At Various Levels Of Regmentioning
confidence: 99%